b)\(\frac{A}{B}=\frac{2}{1-a}\)
Để a nguyên thì 1-a phải là ước của 2 và \(a\ne1\)
Ư(2)\(\in\){-1;-2;2}
Với 1-a=-1 =>a=2(TM)
1-a=-2 => a=3(TM)
1-a=2 =>a=-1(TM)
Vậy a\(\in\){-1;2;3}
a) Mình giải luôn nên bạn tự viết lại đầu bài nhé!
A=\(\sqrt{3-2\sqrt{3}+1}\left(\sqrt{3}+1\right)=\sqrt{\left(\sqrt{3}-1\right)^2}\left(\sqrt{3}+1\right)=\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)=\left(\sqrt{3}\right)^2-1^2=3-1=2\)B=\(\left(1-\frac{a+\sqrt{a}}{\sqrt{a}+1}\right)\left(1+\frac{a+\sqrt{a}}{\sqrt{a}+1}\right)=1^2-\left(\frac{a+\sqrt{a}}{\sqrt{a}+1}\right)^2=1-\left(\frac{\sqrt{a}\left(\sqrt{a}+1\right)}{\sqrt{a}+1}\right)^2=1-\left(\sqrt{a}\right)^2=1-a\)(\(a\ge0\))